Gradual Recovery from Nonambulatory Quadriparesis Caused by Metastatic Epidural Cervical Cord Compression in an Octogenarian Gallbladder Carcinoma Patient Treated with Image-Guided Three-Dimensional Conformal Radiotherapy Alone Using a Field-in-Field Technique - Kazuhiro Ohtakara; Hiroaki Hoshi (Case Reports in Oncological Medicine)
Radiotherapy for acute metastatic epidural spinal cord compression (MESCC) involves conventional techniques and dose fractionation schemes, as it needs to be initiated quickly. However, even with rapid intervention, few paraplegic patients regain ambulation. Here, we describe the case of a mid-octogenarian who presented with severe pain and nonambulatory quadriparesis attributable to MESCC at the fifth cervical vertebra, which developed 10 months after the diagnosis of undifferentiated carcinoma of the gallbladder. Image-guided three-dimensional conformal radiotherapy (IG-3DCRT) was started with 25 Gy in 5 fractions followed by a boost of 12 Gy in 3 fractions, for which a field-in-field (FIF) technique was used to optimize the dose distribution. Despite the fact that steroids were not administered, the patient reported significant pain reduction and showed improved motor function 3 and 4 weeks after the IG-3DCRT, respectively. Over the following 4 months, her neurological function gradually improved, and she was consequently able to eat and change clothes without assistance and to walk slowly for 10–20 m using a walker. She succumbed to progression of abdominal disease 8.5 months after the IG-3DCRT. This case demonstrates that image-guided FIF radiotherapy with a dose-escalated hypofractionated regimen can potentially improve functional outcome and local control.